ANALYSIS OF THE RELATIONSHIP DIAGNOSED MILD COGNITIVE IMPAIRMENT IN ELDERLY AND SENILE PATIENTS WITH CERTAIN FEATURES OF MEDICAL HISTORY AND DEPRESSION - N. N. Maslova; A. Ye. Iusov (Бюллетень сибирской медицины)
Are defined frequency of mild cognitive impairment (MCI) at patients of advanced and senile age with chronic ischemia of a brain (HIGM) in comparison with frequency of existence of a depression, an education level and the place of residence and their interrelation. 100 patients with HIGM 2 age групп: 1 – advanced age (from 60 to 74 years – 48 people), 2 – senile age (from 75 to 89 years – 52 persons) are surveyed. In research didn't join: patients with Alzheimer's disease and other forms of a dementias. Diagnostics of UKN it was carried out by means of a short scale of an assessment of the mental status (MMSE). For an assessment of existence of a depression – Bek's scale. For objective justification of conclusions from results of the carried-out research the statistical analysis of primary information was used.